CLINICAL STUDY ON EFFICACY OF PANCHATIKTA BASTI, TILATAILADI NASYA AND AMRUTADI GUGGULU IN THE MANAGEMENT OF DIABETIC RETINOPATHY (International Journal of Ayurveda and Pharma Research, 2016)
Diabetic retinopathy (DR) is a disease of Dristipatala. Raktapitta, Dosha Avarana and Dhatukshya are the main etiological factors involved. Madhumeha is vatika type of Prameha and all the three Dosha and Saptadhatu except Asthidahtu gets vitiated. Mainly Rakta, Mamsa and Meda dhatu affected by both etiopathological mechanisms of Avarana and Dhatukshya. Agnimandya and Ama formation are initiating factors of the main disease Madhumeha and all these leads to complications similar to Raktapitta due to Rasayani daurvalya. Ojas kshaya is another etiological factor in Madhumeha. In Pranavritta vyana Vyanavayu gets obstructed by Pranavayu and leads to Indriyasunyata. Raktavritta vata too have a role in development of DR Pathology. Timir is described under Vataja nanattmaja vyadhi by Charaka. Vagbhata and Yogratnakara advised Basti chikitsa in Timir vyadhi. By considering the above facts Panchatikta Panchaprasrittika Basti was considered for this trial to reduce pathology of Sira abhisyandam and vasculopathy in diabetic retinopathy cases. Tilatailadi Yoga was considered to reduce hemorrhagic effects in retina and as Nasya is the shortest and effective route for CNS drug delivery for vision improvement, Tilatailadi Nasya was considered for this study. Amrutadi Guggulu was considered for this study, as it has anti-inflammatory, antioxidant, hypolipidemic and above all Srotosodhaka properties, which is particularly indicated for Timir vyadhi. Thus in present study an attempt has been made to prevent and check the progression of different stages of non proliferative stages of diabetic retinopathy (NPDR). Mixed results were obtained with statistically significant improvement in visual acuity, fundus signs and laboratory parameters.